2013
DOI: 10.1016/j.jacc.2012.08.1019
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Predictors in the Use of Aldosterone Antagonists Post-Acute Myocardial Infarction

Abstract: Although rates of aldosterone antagonist use are increasing slightly over time, the vast majority of AMI patients eligible for treatment fail to receive it at hospital discharge. The reason for this discrepancy between guideline-based therapy and actual prescribing patterns is unclear and should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 15 publications
0
39
1
Order By: Relevance
“…Utilization rates of anti-platelet therapy, statin and angiotensin-converting enzyme inhibitor (ACEI)/ angiotensin II receptor blocker (ARB) therapies were as high as previous studies, 12,17 but β-blockers were prescribed to fewer patients when compared to recent reports, although the additive effect of β-blockers on ACEI/ARB has been reported from Japan. [18][19][20][21][22] In addition, 2-year post-discharge observations indicated a potential decrease in adherence to pharmacological therapies. It is well-known that the increase in adherence to treatment guidelines is associated with a lowering of long-term mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Utilization rates of anti-platelet therapy, statin and angiotensin-converting enzyme inhibitor (ACEI)/ angiotensin II receptor blocker (ARB) therapies were as high as previous studies, 12,17 but β-blockers were prescribed to fewer patients when compared to recent reports, although the additive effect of β-blockers on ACEI/ARB has been reported from Japan. [18][19][20][21][22] In addition, 2-year post-discharge observations indicated a potential decrease in adherence to pharmacological therapies. It is well-known that the increase in adherence to treatment guidelines is associated with a lowering of long-term mortality.…”
Section: Resultsmentioning
confidence: 99%
“…In a large survey of eligible hospitalized HF patients, Albert et al [10] reported a modest increase in the rate of MRA use from 28% to 34%, and similar rates were reported in HF surveys in an outpatient setting [11,19]. A recent analysis of the Get with the Guidelines-Coronary Artery Disease national database in 2006-2009 showed a mild increase in MRA prescription rate from 6% to 13.4% [12]. MRA utilization in this study was associated with LVEF reduction, preserved renal function, smoking and revascularization.…”
Section: Discussionmentioning
confidence: 79%
“…However, despite the robust evidence of the benefits of MRAs, this class of medications has been underutilized in eligible chronic HF patients [10,11]. A recent retrospective analysis of the Get with the Guidelines-Coronary Artery Disease cohort showed that MRAs are also underutilized in post-MI patients [12]. However, inclusion criteria of this study were based on a history of HF symptoms prior to the index MI, and thus the study may have failed to include an important subset of MRA-eligible post-MI patients with onset of HF symptoms following the index event in whom, this mode of medical therapy may be underutilized.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several observational and retrospective studies have reported a large gap between the recommendations in the abovecited guidelines and real-world practice in the use of RAASi therapies [30][31][32][33][34][35][36][37]. A retrospective analysis of data from the American Heart Association's Get With the Guidelines: Coronary Artery Disease database reported that less than 10% of eligible heart failure (HF) patients hospitalized for myocardial infarction were prescribed an aldosterone agonist at discharge [32].…”
Section: Raasi Paradoxmentioning
confidence: 99%